2018
DOI: 10.3389/fneur.2018.00683
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Features of Spinal Cord Injury in China: A Systematic Review

Abstract: Background: Spinal cord injury (SCI) is a severe condition that disrupts patients' physiological, mental, and social well-being state and exerts great financial burden on patients, their families and social healthcare system. This review intends to compile studies regarding epidemiological features of SCI in China.Methods: Searches were conducted on PubMed, EMBASE, Web of Science and Cochrane Library for relevant studies published through January, 2018. Studies reported methodological and epidemiological data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 50 publications
1
42
0
1
Order By: Relevance
“…A recent systematic review that included 17 studies in China showed that the epidemiological features of SCI vary among different regions of China; therefore, targeted prevention interventions should be implemented by region. Further, SCI resulting from falls and MVCs may become a major public health concern as the population ages and the economy continues to develop in China [10]. Compared to other areas of China, northwest China has several unique characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review that included 17 studies in China showed that the epidemiological features of SCI vary among different regions of China; therefore, targeted prevention interventions should be implemented by region. Further, SCI resulting from falls and MVCs may become a major public health concern as the population ages and the economy continues to develop in China [10]. Compared to other areas of China, northwest China has several unique characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data have demonstrated that the annual incidence of SCI is 15–40 cases per million and is rising worldwide [ 2 ]. China has a large number of SCI patients, with an estimated incidence of SCI of 60.6 per million in Beijing [ 3 ]. The financial burden associated with SCI is staggering, but despite major advances in the medical treatment for SCI in experimental animals, no fully restorative therapies currently exist for mammalian SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Injuries caused by falls represented 49.8% of cases in Saint Petersburg from 2012 to 2016, and elderly women more often suffered from low falls than men (6). A systematic review on an epidemiological survey of SCI in China showed that falls resulted in 23.9-65.3% of all SCI cases, and that falls were the primary causation of injury in most cities of China (7). Moreover, another retrospective investigation inn Northwest China from 2014 to 2018 showed that falls resulted in 85.1% (low falls 47.7%, high falls 37.3%) of all SCI cases (8).…”
Section: Falls Play An Important Role In Traumatic Spinal Cord Injurymentioning
confidence: 99%